Adjuvant β-Lactam Therapy Combined with Vancomycin or Daptomycin for Methicillin-Resistant Staphylococcus aureus Bacteremia: a Systematic Review and Meta-analysis - Wang, Chunjiang (Antimicrob Agents Chemother, 2020)
Infections due to methicillin-resistant Staphylococcus aureus bacteremia (MRSAB) seriously threaten public health due to poor outcomes and high mortality. The objective of this study is to perform a systematic review and meta-analysis of the current evidence on adjuvant β-lactam (BL) therapy combined with vancomycin (VAN) or daptomycin (DAP) for MRSAB. PubMed, Embase, and Cochrane Library were systematically searched for publications reporting clinical outcomes of BLs+VAN or BLs+DAP for adult patients with MRSAB through 5 April 2020. Meta-analysis techniques were applied using random effects modeling. Three randomized controlled trials and 12 retrospective cohort studies were identified, totaling 2,594 patients. Combination treatment significantly reduced the risk of clinical failure (risk ratio [RR] = 0.80; 95% confidence interval [CI], 0.66 to 0.96; P = 0.02; I(2) = 39%), bacteremia recurrence (RR = 0.66; 95% CI, 0.50 to 0.86; P = 0.002; I(2) = 0%), and persistent bacteremia (RR = 0.65; 95% CI, 0.55 to 0.76; P < 0.00001; I(2) = 0%) and shortened the duration of bacteremia (standardized mean difference [SMD] = –0.37; 95% CI, –0.48 to –0.25; P < 0.00001; I(2) = 0%). There was no significant difference in the risk of crude mortality, nephrotoxicity, or thrombocytopenia between groups. Notably, combination treatment might nonsignificantly increase the risk of Clostridium difficile infection (CDI) (RR = 2.13; 95% CI, 0.98 to 4.63; P = 0.06; I(2) = 0%). Subgroup analysis suggested that DAP+BLs could reduce crude mortality (RR = 0.53; 95% CI, 0.28 to 0.98; P = 0.04; I(2) = 0%). The meta-analysis suggested that although combination therapy with BLs could improve some microbial outcomes, it could not reduce crude mortality but might increase the risk of CDI and should be applied very cautiously. Regarding mortality reduction, the combination of DAP+cephalosporins appears more promising.